Introductory numerical analysis - Pettofrezzo Anthony J (New York Dover, 2006)
Its main theme is interpolation of the standpoint of finite differences, least squares theory, and harmonic analysis. Also covers the numerical solutions of ordinary differential equations and approximation through Fourier series.
Keywords: Numerical analysis